Induction of ovulation in F1 Malaysian mahseer, Tor tambroides (Bleeker, 1854) by using synthetic and non-synthetic hormones - Nik Daud, Nik Md. Azuadi; Siraj, Siti Shapor; Daud, Siti Khalijah; Christianus, Annie; Harmin, Sharr Azni; Sungan, Stephen; Britin, Raymond (Academic Journals, 2013)
Tor tambroides is an important and highly valued freshwater fish. In Malaysia, wild populations of this species has undergone declines in range and abundance due to degradation of their natural habitat. Due to economic important and concerns about their conservation, a culture artificial propagation programme was established to produced seed-stock for aquaculture and conservation purposes. The effectiveness of selected synthetic and non-synthetic commercial hormones was tested on filial 1 generation (F1) of Tor tambroides (Bleeker 1854) females in captivity. A total of 144 matured females were given intramuscular implantation of slow release hormone, Ovaplant (38.6-53.6 μg kg-1 b.wt.), for 5-6 weeks prior to induction. Selected commercial hormones were compared for the induction. The effect of these hormones on breeding performance and larval quality of F1 Tor tambroides were evaluated. The results showed that Ovatide (0.5 mL kg-1 BW) was the most reliable hormone in inducing ovulation of F1 T. tambroides females overshadowed the other tested hormones. Ovaprim (0.5 mL kg-1 b.wt.) was the next best tested hormone followed by a synthetic analogue of salmon gonadotropin releasing hormone (sGnRHa/OvaRH) (10 μg kg-1 b.wt.). No ovulation occurred in the groups treated with Luteinizing Hormone Releasing Hormone Analogue (LHRHa) (10 μg kg-1 b.wt.), Human Chorionic Gonadotropin (HCG) (1000 μg kg-1 b.wt.) and Carp Pituitary Extract (CPE) (10 mg kg-1 b.wt.). Ovatide was further chosen to test its effectiveness at various dosage levels in inducing ovulation of T. tambroides. Thus, concentration of 0.5 mL kg-1 b.wt. of Ovatide was found to be the optimum dosage for inducing ovulation of F1 T. tambroides in captivity.